A Novel Cecropin D-Derived Short Cationic Antimicrobial Peptide Exhibits Antibacterial Activity Against Wild-Type and Multidrug-Resistant Strains of Klebsiella pneumoniae and Pseudomonas aeruginosa. (June 2020) - Ocampo-Ibáñez, Iván Darío; Liscano, Yamil; Rivera-Sánchez, Sandra Patricia; Oñate-Garzón, José; Lugo-Guevara, Ashley Dayan; Flórez-Elvira, Liliana Janeth; Lesmes, Maria Cristina
Infections caused by multidrug-resistant (MDR) Pseudomonas aeruginosa and Klebsiella pneumoniae are a serious worldwide public health concern due to the ineffectiveness of empirical antibiotic therapy. Therefore, research and the development of new antibiotic alternatives are urgently needed to control these bacteria. The use of cationic antimicrobial peptides (CAMPs) is a promising candidate alternative therapeutic strategy to antibiotics because they exhibit antibacterial activity against both antibiotic susceptible and MDR strains. In this study, we aimed to investigate the in vitro antibacterial effect of a short synthetic CAMP derived from the ΔM2 analog of Cec D-like (CAMP-CecD) against clinical isolates of K pneumoniae (n = 30) and P aeruginosa (n = 30), as well as its hemolytic activity. Minimal inhibitory concentrations (MICs) and minimal bactericidal concentrations (MBCs) of CAMP-CecD against wild-type and MDR strains were determined by the broth microdilution test. In addition, an in silico molecular dynamic simulation was performed to predict the interaction between CAMP-CecD and membrane models of K pneumoniae and P aeruginosa. The results revealed a bactericidal effect of CAMP-CecD against both wild-type and resistant strains, but MDR P aeruginosa showed higher susceptibility to this peptide with MIC values between 32 and >256 μg/mL. CAMP-CecD showed higher stability in the P aeruginosa membrane model compared with the K pneumoniae model due to the greater number of noncovalent interactions with phospholipid 1-Palmitoyl-2-oleyl-sn-glycero-3-(phospho-rac-(1-glycerol)) (POPG). This may be related to the boosted effectiveness of the peptide against P aeruginosa clinical isolates. Given the antibacterial activity of CAMP-CecD against wild-type and MDR clinical isolates of P aeruginosa and K pneumoniae and its nonhemolytic effects on human erythrocytes, CAMP-CecD may be a promising alternative to conventional antibiotics.